A prediction model of liver fat fraction and presence of non-alcoholic fatty liver disease (NAFLD) among patients with overweight or obesity - Jie Chen; Jiang Yue; Jingjing Fu; Shengyun He; Qianjing Liu; Minglan Yang; Wang Zhang; Hua Xu; Qing Lu; Jing Ma (Endocrine Journal)
The global prevalence of non-alcoholic fatty liver disease (NAFLD) has attained a level of 25.24%. The prevalence of NAFLD in China has exhibited an upward trajectory in parallel with the increasing incidence of obesity over the preceding decade. In order to comprehensively assess hepatic lipid deposition in individuals with overweight or obesity, we have devised a pioneering prognostic formula that capitalizes on clinical parameters. To this end, we have conducted a cross-sectional cohort study involving 149 overweight or obese subjects. Magnetic resonance imaging proton density fat fraction (MRI-PDFF) has been employed to evaluate the extent of liver fat accumulation. Through univariate analysis, we have identified potential factors, and the definitive elements in the prediction model were selected utilizing the forward stepwise regression algorithm. The Shang Hai Steatosis Index (SHSI) incorporates alanine aminotransferase (ALT), aspartate aminotransferase (AST), fasting insulin, and 1-h postload glycaemic levels, thereby furnishing the capability to predict NAFLD with an area under the receiver operator characteristic (AUROC) of 0.87. By establishing a threshold value of 10.96, determined through Youden’s index, we have achieved a sensitivity of 69.57% and a specificity of 88.24%. The Spearman correlation coefficient between liver fat fraction ascertained by MRI-PDFF and that predicted by the SHSI equation amounts to 0.74. Consequently, the SHSI equation affords a dependable means of predicting the presence of NAFLD and liver fat accumulation within the overweight and obese population.